Distribusi Penyakit Infectious Myo Necrosis Virus (IMNV) Pada Udang Vannamei (Litopenaeus vannamei) Di Pantai Utara Jawa Timur [ Distribution Of Infectious Myo Necrosis Virus (IMNV) In White Shrimp Vannamei (Litopenaeus vannamei) In North Coast, East Java] - Laksmi Sulmartiwi; Andre Rekasana; Sudarno Sudarno (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract White shrimp vannamei (Litopenaeus vannamei) is the main commodities among shrimp farmers because it has a rapid growth, can be cultivated with high density and world market demand is large enough .Since being introduced in Indonesia, vannamei shrimp has spread to the north of East Java pesisisr like Probolinggo, Pasuruan, Lamongan and Tuban. Shrimp growth factors are must be faced on vannamei shrimp culture, including the problems of disease. One type of virus disease is an Infectious Myo Necrosis Virus (IMNV). IMNV has affecting to the 70% of shrimp mortality (Tang et al., 2008). This study aims to determine the distribution of IMNV on white shrimp vannamei from the northern coast of East Java. This research uses descriptive method by taking samples from five different location which 75 samples totaly. In this research also take the water quality parameter including pH, DO, salinity and temperature. Whole of the samples performed the PCR test to determine how many samples which is indicating of IMNV. Based on measurements of water quality at five different locations, the plots I, II and III obtained the temperature range between 29.3-30.2 °C, salinity 90-30 ppt, pH 7.5-7.9, and DO 3.8-5.7 ppm. Temperature, pH and DO parameters show normally on white shrimp vannamei, while salinity shows different valve from normal conditions. Abnormallity happened in Situbondo with the salinity betwen 32-33 ppt and Pasuruan betwen 9-10 ppt. Results showed that the number of the lowest infection is Lamongan (53%) following Probolinggo (60%), Tuban (67%), Pasuruan (73%) and the highest is from Situbondo (100%)